On the information in extreme measurements for parameter estimation. Issue 1 (January 2020) - Ostrometzky, Jonatan; Messer, Hagit
Abstract: This paper deals with parameter estimation from extreme measurements. While being a special case of parameter estimation from partial data, in scenarios where only one sample from a given set of K measurements can be extracted, choosing only the minimum or the maximum (i.e., extreme) value from that set is of special interest because of the ultra-low energy, storage, and processing power required to extract extreme values from a given data set. We present a new methodology to analyze the performance of parameter estimation from extreme measurements. In particular, we present a general close-form approximation for the Cramer–Rao Lower Bound on the parameter estimation error, based on extreme values. We demonstrate our methodology on the case where the original measurements are exponential distributed, which is related to many practical applications. The analysis shows that the maximum values carry most of the information about the parameter of interest and that the additional information in the minimum is negligible. Moreover, it shows that for small sets of iid measurements (e.g. K =15) the use of the maximum can provide data compression with a factor of 15 while keeping about 50% of the information stored in the complete set. We demonstrate our results on a real-world application of rain monitoring.